1996
DOI: 10.1161/01.cir.93.5.870
|View full text |Cite
|
Sign up to set email alerts
|

Activated Partial Thromboplastin Time and Outcome After Thrombolytic Therapy for Acute Myocardial Infarction

Abstract: Although the relationship between aPTT and clinical outcome was confounded to some degree by the influence of baseline prognostic characteristics, aPTTs higher than 70 seconds were found to be associated with higher likelihood of mortality, stroke, bleeding, and reinfarction. These findings suggest that until proven otherwise, we should consider the aPTT range of 50 to 70 seconds as optimal with intravenous heparin after thrombolytic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
1
7

Year Published

1997
1997
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 262 publications
(119 citation statements)
references
References 29 publications
3
108
1
7
Order By: Relevance
“…The agreement between POC aPTT and central laboratory aPTT in controls were found to be better, confirming previous data. [1][2][3][4][5][6][7][11][12][13][14] Our results are partly in line with other studies which have evaluated POC in cardiac surgery patients. Reich et al 8 studied 141 patients and considered an accuracy of ± 10% and a precision of ± 25% as clinically acceptable.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The agreement between POC aPTT and central laboratory aPTT in controls were found to be better, confirming previous data. [1][2][3][4][5][6][7][11][12][13][14] Our results are partly in line with other studies which have evaluated POC in cardiac surgery patients. Reich et al 8 studied 141 patients and considered an accuracy of ± 10% and a precision of ± 25% as clinically acceptable.…”
Section: Discussionsupporting
confidence: 87%
“…[1][2][3][4] Such delays hinder rapid diagnosis of coagulation disorders and adequate anticoagulation to be achieved rapidly. Rapid knowledge of aPTT results should allow the implementation of measures to decrease bleeding as well as the prevention of thrombotic complications.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive anticoagulation with heparin resulting in activated partial thromboplastin time levels above the therapeutic range is not only associated with increased bleeding, but also with an excess of recurrent ischemic events (34). The use of enoxaparin in older patients in the ASsessment of the Safety and Efficacy of a New Thrombolytic regimen (ASSENT)-3 trial (35) was associated with increased intracranial hemorrhage, but the Enoxaparin and Thrombosis Reperfusion for Acute myocardial infarCtion Treatment (ExTRACT) trial (36) showed a reduced-dosage regimen of enoxaparin to be safe in elderly patients (37).…”
Section: Intracranial Hemorrhage and Thrombolysismentioning
confidence: 99%
“…41 Activated Clotting Time ACT measurements are performed to monitor unfractionated heparin therapy during coronary angioplasty and bypass surgery. During angioplasty, values Ͻ250 seconds are associated with an increased incidence of major complications.…”
Section: Activated Partial Thromboplastin Timementioning
confidence: 99%